2019
DOI: 10.1021/acs.jafc.8b06414
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Microbiota Diversity by Lactose-Free Milk in a Mouse Model of Elderly Gut Microbiota

Abstract: Prebiotics may improve ageing-related dysbiosis. Milk is a source of nutrients including oligosaccharides whose prebiotic potential remains largely unexplored. We used a murine model to explore the effect of milk products on high diversity and lower diversity faecal microbiota from healthy and frail elderly subjects, respectively. Mice were treated with antibiotics and subsequently "humanised" with human faecal microbiota. The mice received lactose-free or whole milk, glycomacropeptide, or soy protein (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
(175 reference statements)
1
13
0
Order By: Relevance
“…However, Bacteroidetes group was decreased compared to the baseline. In accordance with our results, Ntemiri et al also found out that whole milk consumption was associated with an increase in taxons belonging to Firmicutes and a higher Firmicutes/Bacteroidetes ratio [76]. In another randomized cross–over study, consumption of probiotic yogurt and milk acidified with D-(+)-glucono-δ-lactone showed some distinct effects on microbiota composition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Bacteroidetes group was decreased compared to the baseline. In accordance with our results, Ntemiri et al also found out that whole milk consumption was associated with an increase in taxons belonging to Firmicutes and a higher Firmicutes/Bacteroidetes ratio [76]. In another randomized cross–over study, consumption of probiotic yogurt and milk acidified with D-(+)-glucono-δ-lactone showed some distinct effects on microbiota composition.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from fermentation, unfermented dairy products may also affect the gut microbiota [75,76]. In our study, regular milk consumption that was used as control also led to some changes in microbiota composition compared to the baseline.…”
Section: Discussionmentioning
confidence: 77%
“…The pipeline for the microbiota composition analysis was described before [48] and comprised the following steps. Paired-end reads were joined with FLASH [49] and quality filtering was performed in Qiime (v.1.9.1) using the split_libraries_fastq.py script [50].…”
Section: Microbiota Composition and Statistical Analysismentioning
confidence: 99%
“…In all, the developed pipeline avoids overlooking the less abundant species, while at the same time resulting on a better understanding of the analyzed microbial populations. Since this methodology allows for a full understanding of any 16S RNA sequencing dataset, it has the potential to unravel the dynamics of other microbial ecosystems important for the agricultural and food chemistry field, such as in food fermentation processes [8] or to study the gut microbiota [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of anaerobic digestion processes, the analysis of the microbial communities can provide an insightful link between the physicochemical state of these digesters and the growth of the microorganisms [7][8][9]. Therefore, in waste AcoD, this analysis is not only useful for obtaining a microbial characterization of the digestion process but also to determine the digester conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%